A training programme for professional nurses to support patients in disclosing HIV-Positive status to sexual partners at selected public hospitals in Limpopo Province, South Africa - Mamogobo, P. M. (University of Limpopo, 2019)
The ability of professional nurses to support and motivate people living with HIV and AIDS to disclose to sexual partner continue to be a challenge based on the social, economic, psychological and ethical circumstances that surround the process to do so. A qualitative research study using semi-structured interviews with a schedule guide whereby probing questions were used to elicit more data. Two focus groups with 6 professional nurses were also conducted to explore and describe professional nurse’s knowledge and practices as they support People Living With HIV and AIDS (PLWHA) to disclose their positive status to sexual partners. The interviews were carried out in five (5) district hospitals of Limpopo Province, South Africa. Dickoff, James, and Wiedenbach (1968) practice theory guided the study. Study findings revealed that professional nurses do understand the concept but however it is difficult for them to translate and link learning and understanding in the clinical area. Social, economic, psychological and ethical dilemmas pose a challenge for professional nurses to support individuals to disclose to sexual partners. Professional nurses refer individuals with challenges to psychologists and social workers, but however, they do not receive referral back on the outcome. The absence of support groups and link with community-based groups to support PLHWA reduce efforts to improve knowledge on benefits of disclosure to communities led by PLHWA including reduction of stigma and discrimination associated with the diagnosis. The study therefore, recommends a training programme that links the South African Nursing Council statutes, including that of World Health Organization and Department of Health with teaching and learning methods that clarify and simulate real clinical situation to enhance the translation of this policy in the real-life situation. The training programme further suggests a link with community base structures led by PLWHA to enhance disclosure of HIV positive status to a sexual partner, reduction of stigma and discrimination associated with the diagnosis and reduce the incidence of HIV among people living with HIV. Key words: People living with HIV infection, Professional nurses, disclosure of HIV to sexual partners
Thesis (PhD. (Nursing Science)) --University of Limpopo, 2019
Keywords: People living with HIV infection; Professional nurses; Disclosure of HIV to sexual partners; AIDS (Disease) - Patients; HIV-positive persons